Angiopoietin-1 Requires Oxidant Signaling through p47phox to Promote Endothelial Barrier Defense - Ghosh, Chandra C.; Mukherjee, Aditi; David, Sascha; Milam, Katelyn E.; Hunter, Jon T.; Parikh, Samir M. (PloS one, 2015)
Reactive oxygen species (ROS) are largely considered to be pathogenic to normal endothelial function in disease states such as sepsis. We hypothesized that Angiopoietin-1 (Angpt-1), an endogenous agonist of the endothelial-specific receptor, Tie-2, promotes barrier defense by activating NADPH oxidase (NOX) signaling. Using primary human microvascular endothelial cells (HMVECs), we found that Angpt-1 stimulation induces phosphorylation of p47phox and a brief oxidative burst that is lost when chemical inhibitors of NOX activity or siRNA against the NOX component p47phox were applied. As a result, there was attenuated ROS activity, disrupted junctional contacts, enhanced actin stress fiber accumulation, and induced gap formation between confluent HMVECs. All of these changes were associated with weakened barrier function. The ability of Angpt-1 to prevent identical changes induced by inflammatory permeability mediators, thrombin and lipopolysaccharides (LPS), was abrogated by p47phox knockdown. P47phox was required for Angpt-1 to activate Rac1 and inhibit mediator-induced activation of the small GTPase RhoA. Finally, Angpt-1 gene transfer prevented vascular leakage in wildtype mice exposed to systemically administered LPS, but not in p47phox knock out (p47-/-) littermates. These results suggest an essential role for NOX signaling in Angpt-1-mediated endothelial barrier defense against mediators of systemic inflammation. More broadly, oxidants generated for signal transduction may have a barrier-promoting role in vascular endothelium.